Folklore and Educational Administration in Alaska: An Ethnographic Study of Rural School Administration - C. Douglas Rider (Journal of Research in Rural Education, 1982)
This paper describes the use of folklore (the telling of tales, stories, etc.) by school administrators in five rural Alaskan communities as a tool for communication of complex cultural issues. It is suggested that occupational phenomena as well as cross-cultural ideas are communicated and that such communication is important in recruiting and retaining school administrators in such settings